THE ARTISTIC AESTHETICS AS AN EFFECTIVE TOOL IN PACKAGING DESIGN FOR THE ELDERLY - Jun, Li; Dubrivna, Antonina Petrivna (Theory and practice of design, 2025)
Abstract. Purpose: analyze the design of senior friendly packaging through the theoretical framework of art criticism, and explore the integration path of formal, functional and emotional beauty, in order to break the traditional design paradigm, and create a more humanistic and to offer design opportunities to create a more humane and aesthetic living environment for the elderly. Methodology is based on the theory of aesthetics in design, and the study is based on three dimensions: formal beauty (visual perception), functional beauty (human-computer interaction), and emotional beauty (cultural identity); a comparative method is used to identify examples of seniors’ packaging design in China and abroad to explore specific strategies for applying artistic aesthetics in seniors’ packaging. Results. It is found that the combination of artistic aesthetics of senior friendly packaging design can significantly enhance the use experience of elderly users. At the level of formal beauty, high-contrast colour combinations and simple graphics can significantly enhance the visual recognition of elderly users; at the level of functional beauty, ergonomic grip structure and layered information design can effectively reduce the difficulty of operation; at the level of emotional beauty, packaging that incorporates regional cultural symbols or family memory elements can enhance the emotional resonance of elderly users. Scientific novelty. The study extends the understanding of established packaging design for seniors that focuses only on functionality; for the first time, aesthetic theory is applied to packaging design, offering an interdisciplinary research framework of “integrating the three aesthetics”. The combination of quantitative and qualitative analysis reveals the deep connection between aesthetic elements and elderly consumers’ behaviors and emotions, providing theoretical support for inclusive design. In addition, the construction of a case database and empirical study of the needs of elderly consumers demonstrates a new paradigm for further design practice. Practical relevance. The findings of the study can directly guide the innovative practice of ageing-friendly packaging design, help enterprises to develop products that meet the needs of the elderly and enhance market competitiveness, and promote the transformation of the design industry from “object-centred” to “human-centred”, so as to promote intergenerational tolerance and social harmony.